Pengaruh Promosi Jabatan, Tunjangan Kinerja dan Kepemimpinan Terhadap Kinerja Pegawai Pada Kantor BKKBN Kota Bima - Nini Safriani; Wulandari; Mukhlis (Formosa Journal of Social Sciences (FJSS), 2022)
This study aims to determine the effect of promotion, performance allowance and leadership on employee performance at the Bima City BKKBN Office. This research is included in the category of associative research using a quantitative approach. The number of samples is 32 people using the Purposive Sampling technique with the criteria that only employees are civil servants at the Bima City BKKBN office. Based on the results of the partial test (t test) shows that there is a positive and significant effect on the variable of job promotion on employee performance. Variables of performance allowances and leadership have no effect on employee performance at the Bima City BKKBN Office. But simultaneously (simultaneously) all variables have a significant effect on employee performance at the Bima City BKKBN Office